Capacidade tecnológica territorial : conceito, modelo e aplicações - Santos, Carlos Eduardo Silva (Universidade Federal de São Carlos, 2017)
The territory presents itself as a space of analysis where several elements are considered and attributes can, in the delimitation and in the understanding of its development dynamics be used. This work is based on the premise that territories have a set of characteristics that stimulate or hinder the technological development of their socioeconomic agents. This thesis advocates that in addition to discussing and identifying these factors, it is important to measure them in the most objective way possible. In this multifaceted framework of development, technological innovations are seen as important determinants of competitiveness. In fact, the search for technological and managerial resources, whether public or private, to increase competitiveness, goes beyond the scope of entrepreneurial ventures and even agroindustrial systems, reaching the territories and regions. A significant part of the Brazilian municipalities has its socio-productive activities based on the rural environment and agribusiness. Knowing the technological capability of territories can provide relevant subsidies for the application of public policies that stimulate the generation, transfer and adoption of agricultural technological innovations contributing to territorial development. This situation emphasizes the importance of evaluating the capability of a given territory to provide favorable conditions for the technological development of socioeconomic agents and their agroindustrial chains. The objective of this work is to establish a concept and propose a model of measurement of territorial technological capability, verifying its empirical applicability in a territory for determined agroindustrial production systems. Based on the literature review was established the concept and proposed a model of measurement of territorial technological capability. Through a case study in the territory of Northwest Paulista, interviews were conducted with agents that support innovation in agriculture, related to productive chains of eggs and rubber, with the application of structured questionnaires. The proposed concept opens the possibility of approaching the technological development of territories under a new perspective, offering subsidies for this development with a focus on agroindustry chains. The model presents different results for the territorial technological capability in relation to the egg and rubber production system in the Northwest of São Paulo. The territory presents an intermediate level of technological capability for the production of eggs and a pre-advanced level for the production of rubber. This sensitivity of the model is expressed in a general indicator, as well as in specific indicators related to the dimensions, elements and descriptors that characterize the model.
Keywords: Capacidade tecnológica territorial; Desenvolvimento territorial; Inovação tecnológica; Cadeia agroindustrial; Capacidade tecnológica; Territorial technological capability; Territorial development; Technological innovation; Agroindustrial chain; Technological capability; ENGENHARIAS::ENGENHARIA DE PRODUCAO